2018
DOI: 10.3389/fmicb.2018.00976
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Limit-Fed Diets With Different Forage to Concentrate Ratios on Fecal Bacterial and Archaeal Community Composition in Holstein Heifers

Abstract: Limit-feeding of a high concentrate diet has been proposed as an effective method for improving feed efficiency and reducing total manure output of dairy heifers; meanwhile the effects of this method on hindgut microbiota are still unclear. This study investigated the effects of a wide range of dietary forage:concentrate ratios (F:C) on the fecal composition of bacteria and archaea in heifers using next-generation sequencing. Four diets with different F:C (80:20, 60:40, 40:60, and 20:80) were limit-fed to 24 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 68 publications
6
31
2
Order By: Relevance
“…Consistent with the ruminal microbial metabolites, the SFC diet significantly increased the propionate proportion, and the correlation analysis showed that the abundance of Succinivibrio was significantly positively correlated with the propionate concentration. For the genus Roseburia, which could hydrolyze and ferment starch (Stanton et al 2015), the abundance was increased linearly with increasing dietary concentration levels (Zhang et al 2018a). Blautia utilizes carbohydrates as fermentable substrates (Park et al 2013), and its abundance was positively correlated with the propionate concentration in our study.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Consistent with the ruminal microbial metabolites, the SFC diet significantly increased the propionate proportion, and the correlation analysis showed that the abundance of Succinivibrio was significantly positively correlated with the propionate concentration. For the genus Roseburia, which could hydrolyze and ferment starch (Stanton et al 2015), the abundance was increased linearly with increasing dietary concentration levels (Zhang et al 2018a). Blautia utilizes carbohydrates as fermentable substrates (Park et al 2013), and its abundance was positively correlated with the propionate concentration in our study.…”
Section: Discussionsupporting
confidence: 58%
“…The numbers of the phylum Firmicutes are involved in the degradation of starch (Kaoutari et al 2013). The relative abundance of Proteobacteria was increased linearly in dairy heifers fed increasing dietary concentration levels (Zhang et al 2018a), or it was found at relatively higher levels in cattle offered high concentrates diets (Auffret et al 2017). The alteration in the genus Succinivibrio (phylum Proteobacteria) was also observed in this study, and Succinivibrio appears to be a major fermenter of dextrins (Bryant 2015).…”
Section: Discussionsupporting
confidence: 57%
“…Fresh1d indicates fecal microbiota samples from cows on d1, Fresh14d indicates fecal microbiota samples from cows on d14 cows were fed a low concentrate-to-forage diet and then switch to a high concentrate-to-forage diet. A large body of work points that the composition of the bovine foregut (Clemmons et al 2019;Henderson et al 2015) and hindgut microbiota (Kim et al 2014;Zhang et al 2018) was shaped by the diet; however, this study was not specifically designed to address the effects of specific feedstuffs on the bovine fecal microbiota. More studies are needed to research the effects of diet on fecal microbiota in lactation dairy cows.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that diet can make a significantly influence in the structure of the fecal microbiome (Kim et al 2014 ; Zhang et al 2018 ). However, lactation was found to be another important factor to shape rumen microbiome in dairy cows (Bainbridge et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The previous study showed the relative abundance of Firmicutes increased in high nutrition diets [32], on account of the high energy providing for the microbiota and accelerating their breeding. Meanwhile, Bacteroidetes showed a decrease, suggesting that they cannot compete in the first few days after diet transition [33]. Tenericutes exists in many mammal guts; it includes both beneficial and pathogenic bacterial taxa [34].…”
Section: Discussionmentioning
confidence: 99%